Automatic nutrient mixer and pH Level for hydroponic application / Hariz Akmal Azizan - Azizan, Hariz Akmal (2024)
This project presents the design and development of Automatic Nutrient Mixer and pH Level for Hydroponic Application using an Arduino microcontroller. The system aims to address the limitations of current hydroponic systems by providing efficient monitoring and control. The main objectives of the project are to incorporate IoT technology into a hydroponic system and automate nutrient dosing. The methodology involves utilizing an Arduino microcontroller as the central control unit, along with various sensors to monitor parameters such as nutrient levels, pH, and temperature in real-time. The collected data is processed and transmitted to a user interface or cloud platform, enabling remote monitoring and control. A simulation and hardware were conducted to demonstrate the successful operation of the system, including pH and TDS -controlled nutrient dosing, LDR control LED and DHT11- monitoring temperature. Future work could involve integrating advanced machine learning algorithms to optimize nutrient dosing and implement self-harvesting mechanisms, thereby enhancing plant production and contributing to the development of more efficient and sustainable hydroponic systems for agricultural practices.